Factors influencing the participation of elite Croatian deaf athletes in sports - Vuljanic, A.; Jenko Miholic, S.; Tišma, D. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The primary aim of the research was to identify the factors influencing the participation of elite deaf athletes in Croatia, while the secondary aim was to collect data on their hearing status and their family's hearing status, the use of hearing aids and communication methods, educational level, sports initiation, and preferences regarding coaches and competitions. The research was conducted on a sample of 31 elite deaf athletes (20 men and 11 women) from seven sports. A questionnaire on the participation of elite deaf athletes in sports was used, encompassing structured sections related to influencing factors. All surveyed deaf athletes participate in domestic competitions within the regular competition system alongside hearing athletes, which plays an important role in their integration into the hearing community. The results of the research indicate a desire among deaf athletes for greater opportunities to participate in their chosen sport, often necessitating their integration into the standard sports system. It is also confirmed the positive role of parents in supporting and nurturing their child's desire to engage in sports. Most elite Croatian deaf athletes begin participating in sports during the upper grades of primary school, highlighting the need for increased promotion of the importance of including children with hearing impairments in sports activities, as well as raising awareness among parents and professionals in health and educational institutions about the possibilities of including children with hearing impairments in both regular and deaf sports systems from an early age.